First record of the Indo-Pacific areolate grouper Epinephelus areolatus (Forsskål, 1775) (Perciformes: Epinephelidae) in the Mediterranean Sea - Rothman, Shevy B.s.; Stern, Nir; Goren, Menachem (Zootaxa, 2016)
The number of alien species in the Mediterranean Sea is steadily increasing and it seems that the pace has been accelerating since the turn of the century (Galil et al. 2014). In 2015 alone five additional fish species have been reported, Epinephelus geoffroyi (Klunzinger, 1870) (Golani et al. 2015); Stolephorus indicus (van Hasselt, 1823) (Fricke et al. 2015); Sardinella gibbosa (Bleeker, 1849) (Stern et al. 2015); Mobula japanica (Müller & Henle, 1841) (Capapé et al. 2015); and Cryptocentrus caeruleopunctatus (Rüppell, 1830) (Rothman & Goren 2015). Among the ca. 100 alien fish species reported from the Mediterranean to date (Galil & Goren 2014), five Indo-Pacific species belong to the genus Epinephelus Bloch, 1793: Epinephelus coioides (Hamilton, 1822), Epinephelus fasciatus (Forsskål, 1775), Epinephelus malabaricus (Bloch and Schneider, 1804) Epinephelus merra Bloch, 1793 (Golani et al. 2013a) and Epinephelus geoffroyi (Klunzinger, 1870) (Golani et al. 2015). Additional alien Epinephelus species reported from the Mediterranean are excluded for various reasons (Golani et al. 2013b). Here we report the finding of a sixth Indo-Pacific species of this genus along the Mediterranean coast of Israel.